Proteomic Sequencing of Stellate Ganglions in Rabbits With Myocardial Infarction - Cheng, Lijun; Wang, Xinghua; Chou, Hongda; Liu, Tong; Fu, Huaying; Li, Guangping (Frontiers in Physiology, 2021)
The stellate ganglion (SG) of the autonomic nervous system plays important role in cardiovascular diseases (CDs). Myocardial infarction (MI) is associated with sustained increasing cardiac sympathetic nerve activity. Expressions and functions of proteins in SG tissue after MI are remaining unclear. This study is to explore the expression characteristics of proteins in SGs associated with MI. Japanese big-ear white rabbits (n = 22) were randomly assigned to the control group and MI group. The MI model was established by left anterior descending coronary artery ligation and confirmed by serum myocardial enzymes increasing 2,3,5-triphenyltetrazolium (TTC) staining and echocardiography. The expressions of proteins in rabbit SGs after MI were detected using tandem mass tags (TMT) quantitative proteomic sequencing. There were 3,043 credible proteins were predicted in rabbit SG tissues and 383 differentially expressed proteins (DEPs) including 143 upregulated and 240 downregulated proteins. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis showed that the DEPs involved in adrenergic signaling in cardiomyocytes, positive regulation of ERK1 and ERK2 cascade, and other biological processes. Three kinds of proteins directly correlated to CDs were selected to be validated by the subsequent western blot experiment. This study first identified the characterization of proteins in rabbit SG after MI, which laid a solid foundation for revealing the mechanism of roles of SG on the MI process.